Impact of Calcium Lactate Concentration and Holding Time on Caviar-like Chicken Broth Hydrogel Beads - Karslioglu, B; Soncu, ED; Kizildogan, T; Gezer, D; Almaci, SS (Molecules)
This study is the first to encapsulate chicken broth into caviar-like hydrogel beads (CBHBs) using ionic gelation, aiming to explore their potential in molecular gastronomy and functional food design. The effects of calcium lactate concentration (1%, 2.5%, and 5%) and post-gelation holding time (0, 30, and 60 min) on the physicochemical, morphological, mechanical, and sensory properties of chicken broth hydrogel beads were evaluated. The beads were produced by dropping a 1% sodium alginate-chicken broth mixture into calcium lactate solutions, followed by analysis of diameter, bulk density, pH, color, shape, texture, and consumer acceptance. Results revealed that higher calcium concentrations and extended holding times significantly decreased bead diameter and increased bulk density and hardness, indicating denser and more compact structures. Morphologically, increased calcium levels resulted in irregular, droplet-like shapes, with reduced sphericity. Instrumental color analysis showed higher a*, b*, and chroma values at higher calcium levels. Sensory evaluations demonstrated that samples with lower calcium concentrations and no post-gelation holding were significantly preferred by panelists in terms of softness and overall liking. These findings underscore the importance of optimizing calcium concentration and holding time in the design of alginate-based hydrogel beads and suggest that CBHBs have potential applications in molecular gastronomy and functional food product development.
Keywords: chicken broth; ionic gelation; alginate beads; molecular gastronomy; texture analysis; encapsulation efficiency